Physical Culture and Sports as the Basis for a Healthy Lifestyle for Young People - Samadov Sardor Sadikovich (International Journal on Integrated Education, 2022)
The article examines the aspects of the influence of physical culture and sports on the healthy lifestyle of society, and in particular on the health of adolescents and youth. Positive qualities that can improve the emotional and moral state of people of all ages. Physical education and sports not only provide positive dynamics in the field of health, but also help each person to acquire new skills and abilities.